Kulturowe role płci i dzietność w Polsce i Norwegii - Kocot-Górecka, Katarzyna (Studia Demograficzne, 2015)
Changing gender roles are increasingly considered as a driving factor of both fertility decline in European countries and its recovery in some of these countries. The fertility decline is attributed to the first stage of the gender revolution when increasing women’s labour force participation is accompanied by some progress in gender equality in the public sphere while in the family life a gender asymmetry remains. During the second stage of the gender revolution the progress towards new roles of men and women in the private sphere takes place – they both are considered as economic providers and careers and share work and family responsibilities (e.g. McDonald 2000b, Goldscheider, Bernhardt, Lappegård 2015, Esping-Andersen, Billari 2015). The article compares on-going changes in gender roles in Poland and Norway, two countries which are at different stages of this process, and their interplay with fertility (mean number of children and intensions about the second and third child). Attitudes towards gender equality are studied by taking into account views on this issue on one side and sharing care and housework on the other. Data come from the first round of the Generations and Gender Survey. The study has been performed for respondents aged 20–44, living together with a partner and children under 14 years of age. The descriptive analyses showed that Poles are not only less advanced in gender role changes in two gender dimensions studied: their views on gender roles are more traditional than Norwegian ones, women’s share in family duties is higher contrary to men who contribute less to family responsibilities than women and men in Norway. There is also a higher variation of views and practices among Poles. In Poland and Norway, egalitarian men participate more in family duties than those who declare traditional views, while egalitarian women are less burdened by home work and care. However, in Norway there is remarkably more egalitarian women with low and medium share of domestic duties in parallel to more numerous egalitarian men who take a great share of family responsibilities. More egalitarian respondents have fewer children than the traditional ones in both countries. However, the mean number of children among this group of respondents in Norway is higher than in Poland. Moreover, women in both countries are less inclined to declare intensions to have a second or third child when they participate more in care and domestic duties. This relationship has been found for men in Norway as well.